Studies on the effect of caffeine on the growth rate of ipomoea aquatic / Nur Nazihah Mohd Hanafi ... [et al.] - Mohd Hanafi, Nur Nazihah; Nadhirah Azni, Nur Azizah; Jahabar Maraikan, Hanan Hasina; Wan Mokhtar, Wan Nur Farisha Alya; Nor Azam, Nor Azwin; Kamarulzaman, Ahmad Faris Seman (Universiti Teknologi MARA Cawangan Pahang, 2020)
Ipomoea aquatica is a type of plant full of nutritional values. In increasing its production, chemical fertilizers are frequently used by farmers. An uncontrolled usage of chemical fertilizers, however, may cause environmental damage. Recently, large amounts of coffee residues are generated and reported to be used as a greener alternative fertilizer. The effect of caffeine in coffee residue has not yet been tested on I. aquatica. Hence, this research aims to determine the effect of caffeine in coffee residue towards I. aquatica and soil pH. The I. aquatica seedlings are divided into 5 groups with 5 seedlings in each group. Three groups are treated with 0.35% (w/v), 0.20% (w/v) and 0.05% (w/v) of caffeine while the other two groups are watered with AB fertilizer and tap water as positive and negative controls respectively. The caffeine treatment in this study shows no significant difference in the growth of I. aquatica even though it has changed the pH of the soils. However, the change of pH value still falls within the range of an optimum pH for I. aquatica, which is between 5.5 to 7 pH. The results of this study, on the other hand, still suggest an excessive use of caffeine. Future studies should be conducted with a lower level of caffeine in obtaining a positive effect of caffeine towards I. aquatica.